Strategi Guru dalam Meningkatkan Literasi Membaca melalui Kegiatan Membaca Nyaring di Kelas Rendah - Siddiq Fahrel; Zakia Faiha; Mutiara Ananda; Afriza Media; Ari Suriani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Low reading interest and skills in early elementary school classes indicate the need for efficient learning strategies. One method that has been proven to improve literacy skills is reading aloud activities. This study aims to explain the strategies implemented by teachers in improving reading literacy skills through reading aloud activities in lower grades. This research method uses a qualitative descriptive approach with data collection techniques through interviews and observations. The findings of the study indicate that reading aloud strategies implemented by teachers, such as selecting interesting picture books, using intonation and expression when reading, and reflecting after reading can increase students' interest and participation in reading activities. This activity also increases students' vocabulary and builds good reading habits. This study emphasizes the significance of teacher training in expressive reading and providing quality reading books in elementary schools.,